Fuzzy logic pro podporu investic do výzkumu a vývoje v malých a středních podnicích - Bočková, Nina (Univerzita Pardubice, 2015)
R&D spending is one of key tools to achieve companies' growth. Government support is key factor for R&D activities in manufacturing small and medium enterprises. The uncertainty of the outcome of research and innovation restricts owners and managers decision on strategic planning about production program of the company. Managers solve additional financing research activities from other sources by the impossibility of full funding from its own budget. Here is presented a fuzzy model-objective - option R&D support which maximizes the outcome and optimizes the R&D program in manufacturing small and medium enterprises. The methodology used a two-stage decision making, using 18 variables, of which two are interdependent. The used of fuzzy logic have been taken because some vaguely specified characteristics that cannot be accurately determined. This method of application offers an innovative look at the funding of R & D activities in the company. The methodology was developed on the basis of data of enterprises of electro technical industry and was verified using data from period 2007-2013.
Fuzzy logic to support of investments in research and development in small and medium-sized businesses
Keywords: research; development; R&D support; innovation policy; small and medium-sized enterprises; H25; L25; O31; O32; O39